2019
DOI: 10.1021/acsapm.9b00565
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Polarization and Electroresponsive Electrorheological Effect of Anionic and Cationic Poly(ionic liquids)

Abstract: Owing to weak ion pair electrostatic interaction and intrinsically hydrophobic nature, poly­(ionic liquids) (PILs) have potentiality as anhydrous polyelectrolyte-based electrorheological (ER) smart materials. Up to now, however, only cationic PILs as ER materials have been studied. In this work, we report the first ER materials based on anionic poly­[4-styrenesulfonyl­(trifluoromethylsulfonyl)­imide tetraethylammonium] (P­[STFSI]­[N2222]) and conduct a comparative study on electroresponsive ER effect with its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…It means the ER fluid without the stimuli of the electric field is more like a viscoelastic liquid. As mentioned above, after applying an electric field, the particles in ER fluids form chains or columns [ 47 , 48 ]. That is why G’ increases by several orders of magnitude and remains constant until strain amplitude reaches a certain value, which is the LVE region.…”
Section: Resultsmentioning
confidence: 99%
“…It means the ER fluid without the stimuli of the electric field is more like a viscoelastic liquid. As mentioned above, after applying an electric field, the particles in ER fluids form chains or columns [ 47 , 48 ]. That is why G’ increases by several orders of magnitude and remains constant until strain amplitude reaches a certain value, which is the LVE region.…”
Section: Resultsmentioning
confidence: 99%
“…At relatively high temperatures, the relaxation peak appears and the peak position moves towards high frequency as the temperature rises. According to the analysis in our previous report [ 29 ], this relaxation process is attributed to the interfacial polarization induced by the movement and accumulation of dissociated PF 6 − at the interface between PIL particles and silicone oil. To get good ER property, it has required ER particles to have not only large interfacial polarizability but also suitable polarization rate because ERFs are usually work under the simultaneous stimuli of electric and shearing fields [ 28 ].…”
Section: Resultsmentioning
confidence: 83%
“…Due to the higher ion number density in the dual-cation PILs, it exhibits higher polarizability and stronger ER response under an electric field. In addition, to study the influence of the chemical structure of the counter cation on the ER effect of anionic PILs, Zhao et al [ 50 , 92 , 126 , 130 ] synthesized poly[4-styrenesulfonyl (trifluoromethylsulfonyl) imide (P[STFSI][X]) with anionic polymer backbone and cationic counterion. It is found that the size of cations did not show a monotonic influence on the ER effect of the PILs.…”
Section: Er Responsesmentioning
confidence: 99%
“…Marins et al reported ILs-assisted silica particles which presented higher permittivity and better ER effect than pure silica particles [ 45 , 46 , 47 ]. Yin et al have done a series of work on designing PILs-based ER materials with various chemical structures in cations and anions [ 48 , 49 , 50 ]. Even though ILs have shown excellent physicochemical properties in other fields, there are still several key issues to be solved when applied as ER materials.…”
Section: Introductionmentioning
confidence: 99%